The Authenticity Gap between what is taught in Bangladeshi EFL Courses and the Reality of authentic English - Tarannum, Sawsan (IIUC Studies, 2016)
The issueI intend to discuss in this paper is one that frustrates teachers and students alike. Bangladeshi students diligently practice their English for varying degrees of time and make varying amounts of progress but seem to run into insurmountable difficulties when confronted with native speaker (NS) English. These difficulties stem from the seeming lack of convergence between the language being used by NSs and the language our students are practicing. In short, there is something of a 'gap' between what is taught in English conversation classes in Bangladesh, and the reality of authentic English. This paper, therefore, briefly focuses on what is meant by the term authenticity gap and the role of text books in relation to this gap. Problems associated with utilizing authentic English in Bangladeshi classrooms will also be discussed in detail. Finally, there will be recommendations on how to bridge this gap. IIUC Studies Vol.12 December 2015: 101-110